Formulating Human Resource Management Strategies Using a Hybrid SOAR–AHP Approach in MSMEs - Shinta Laura Dewani; Diah Ayu Arif Viyanti; Ravita Yosi Agustin; Mutia Tsalitsa Alawia; Wiwik Mukholafatul Farida (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to formulate human resource management (HRM) strategies for a culinary MSME in Kediri using a hybrid SOAR–AHP approach. Rapid business growth is often not accompanied by optimal HR management, leading to issues in performance consistency and employee discipline. This research employs a mixed-method approach with an exploratory sequential design, utilizing interviews, observations, and quantitative analysis through the Analytical Hierarchy Process (AHP). The SOAR analysis reveals that key strengths lie in owner involvement and the existence of standard operating procedures (SOP), while the main challenges relate to consistency in implementation and employee discipline. The AHP results indicate that strengths and results are the highest priority criteria. The main strategies focus on strengthening SOP implementation, improving discipline through active owner supervision, and enhancing work productivity. This study demonstrates that the integration of SOAR–AHP provides more structured, measurable, and applicable HRM strategies to support MSME sustainability.